Gerando modelos de dois campos escalares - Alves Júnior, Francisco Artur Pinheiro (2012)
We focus this work in scalar field theory. We review the basic aspects of models containing one scalar field, like the 4, and the two scalars field theory, like the BNRT. We still review the deformation procedure, in order to generate new soluble one field models. The main result is concerned to a new procedure wich makes possible to generate new two field models and its static solutions.